On the Economy of Machinery and Manufactures - Babbage, Charles, 1791-1871 (Salt Lake City, UT : Project Gutenberg, 2003)
"On the Economy of Machinery and Manufactures" by Charles Babbage is a scientific publication written in the early 19th century. This work explores the principles and advantages of machinery and its impact on manufacturing processes, reflecting on Babbage's extensive observations of factories and workshops across Europe. The book aims to reveal the underlying principles that govern the application of machinery in various industries, emphasizing their economic significance and the evolution of manufacturing practices. At the start of the text, Babbage introduces his work and outlines his motivations for writing it, which stem from his experience with the calculating engine and his visits to numerous manufacturing sites. He emphasizes that the understanding of machinery and its effects on labor is crucial for a country$1 (Bs economic prosperity, urging the wealthier classes to appreciate the significance of industrial advancements. Babbage intends to present a classification of mechanical principles and discusses concepts such as the division of labor, the generation of power through machinery, and the time-saving benefits wrought by technological innovations. His method aims to make these ideas accessible, stripping jargon while providing ample evidence and relatable anecdotes to support his insights into the intricate relationship between machinery and production. (This is an automatically generated summary.)s
Release date is 2003-07-01
This etext was produced by Charles Aldarondo
Keywords: Machinery; Manufactures